Notebook : Issue 2 : We traveled a lot... - Kasman, Daniel (New York : MUBI, Inc., 2022)
Arrivals: Riding with the movie phantoms / Tom Gunning ; Requiem for a city / Joseph Fahim ; Discover, wait, and capture / Park Chan-Wook ; It's grand...and it's central! ; Faraway, so close! a journey through Germany / Pan Lu, Julian Ross, Bo Wang ; Traveling in the dark / Luciano Monteagudo ; Navigating Future Worlds / David Sheldon-Hicks ; Danny Lyon's do-it-yourself distribution / Danny Lyon ; Re: Transmittal of information concerning department of stateless images llc / Miko Revereza ; Fårö document / Dash Shaw ; Una settimana in L.A. (A Week in L.A.) / Michelangelo Antonioni ; Chasing light: A flight to Temenos / Sofia Bohdanowicz ; Living two lives: The one i have in my memory, the other i have now / Natalka Bilotserkivets, Zoya Laktionova ; Departures: Riding with today's phantoms / Notebook
boek